Penerapan Acceptable Quality Level (AQL) Dalam Tahapan Final Inspection Produk Garmen Di PT XYZ - Eki Wulandari Al Masruroh; Endang Pudji Widjajati (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Quality control in the garment industry plays an important role to ensure that the products produced meet high quality standards and satisfy consumers. The Acceptable Quality Level method is a promising approach for optimizing garment product control. This research focuses on the application of the Acceptable Quality Level method in managing garment quality at PT XYZ. The aim is to explore the extent to which this method can be applied efficiently in garment production by considering the existing challenges and opportunities. This study uses the "L Tunic Crinckle" tunic sample from PT XYZ as the research object. Data collection involves primary data from direct interactions and observations, as well as secondary data from related literature and journals. Raw material sampling methods are based on product defects, focusing on attribute data to assess non-compliance with specifications. With an AQL value of 2.5% and general supervision level II, this study took a sample of 125 tunics for inspection. Even though several minor and major defects were found, the total rejects did not exceed acceptance standards, so the tunic product lot could be accepted without re-inspection